Effects of plyometric exercise training with external weights on punching ability of experienced amateur boxers - Bruzas, V.; Kamandulis, S.; Venckunas, T.; Snieckus, A.; Mockus, P. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: During competition, a boxer must continue to deliver high-impact punches despite increasing fatigue. It is unclear whether the effects of plyometric training using external weights are transferred to sport-specific movements such as punching. The aim of the study was to investigate the effects of a 4-week cycle of plyometric training with external weights on punching ability.